Polymeric Microneedles Enhance Transdermal Delivery of Therapeutics - Hiep X. Nguyen; Thomas Kipping; Ajay K. Banga (MDPI AG, 2024)
This research presents the efficacy of polymeric microneedles in improving the transdermal permeation of methotrexate across human skin. These microneedles were fabricated from PLGA Expansorb® 50-2A and 50-8A and subjected to comprehensive characterization via scanning electron microscopy, Fourier-transform infrared spectroscopy, and mechanical analysis. We developed and assessed a methotrexate hydrogel for physicochemical and rheological properties. Dye binding, histological examinations, and assessments of skin integrity demonstrated the effective microporation of the skin by PLGA microneedles. We measured the dimensions of microchannels in the skin using scanning electron microscopy, pore uniformity analysis, and confocal microscopy. The skin permeation and disposition of methotrexate were researched in vitro. PLGA 50-8A microneedles appeared significantly longer, sharper, and more mechanically uniform than PLGA 50-2A needles. PLGA 50-8A needles generated substantially more microchannels, as well as deeper, larger, and more uniform channels in the skin than PLGA 50-2A needles. Microneedle insertion substantially reduced skin electrical resistance, accompanied by an elevation in transepidermal water loss values. PLGA 50-8A microneedle treatment provided a significantly higher cumulative delivery, flux, diffusion coefficient, permeability coefficient, and predicted steady-state plasma concentration; however, there was a shorter lag time than for PLGA 50-2A needles, base-treated, and untreated groups (p < 0.05). Conclusively, skin microporation using polymeric microneedles significantly improved the transdermal delivery of methotrexate.